Imprinting disorders associated with molecular changes on chromosome 11p15 - Weksberg, Rosanna (Henry Stewart Talks, 2014)
What is epigenetics?, Epigenetic regulation forms the molecular basis for genomic imprinting, What is genomic imprinting, Imprinted genes in early development, Genomic organization of imprinted genes, Imprinting center, Imprinted domain 1 on chromosome 11p15.5, Complexity of imprinted clusters, Beckwith-Wiedemann syndrome (BWS), BWS: a complex, clinically heterogeneous disorder, Molecular basis of BWS, Etiology of the Beckwith-Wiedemann syndrome, Molecular alterations associated with BWS, Frequency of molecular alterations in BWS, The risks to subfertile/ART treated parents, Subfertility/assisted reproductive technologies (ART), BWS molecular defects, Multiple phenotypes associated with somatic mosaicism for 11p15 UPD, Somatic mosaicism, Isolated hemihyperplasia, High level constitutional UPD, BWS molecular testing strategies, Laboratory testing for BWS, MS-MLPA, Expected methylation results from MS-MLPA, MLPA molecular testing for BWS, Cancer risk & surveillance, Prenatal testing options, Current challenges in BWS molecular testing, Frequency of CNVs according to methylation pattern, Monozygotic twins and BWS, Isolated hemihyperplasia, Current challenges in chromosome 11p15 molecular testing, Russell-Silver syndrome (RSS, Chromosomal regions associated with RSS, Targeted assays of multiple imprinted loci-BWS, Different combinations of epigenetic alterations associated with variations in clinical phenotype, Imprint deregulation causing disease in humans